Early Detection of Maternal Risk for Preeclampsia. (17th July 2012) - Mikat, B.; Gellhaus, A.; Wagner, N.; Birdir, C.; Kimmig, R.; Köninger, A.
Abstract : Preeclampsia is one of the leading causes of maternal and fetal morbidity and mortality. New molecular insights offer new possibilities of early diagnosis of elevated maternal risk. Maternal risk factors, biophysical parameters like Doppler examination of the uterine arteries and biochemical parameters allow early risk calculation. Preventive and effective therapeutic agents like acetylsalicylacid can be started in the early second trimester. This article reviews the diagnostic possibilities of early risk calculation to detect women having high risk for preeclampsia and the potential benefits for them, the offspring and health care systems. We provide risk calculation for preeclampsia as an important and sensible part of first trimester screening.